(untitled) (Asian Business Research, 2022)
In the changing capital market environment, every trader pursues profit maximization. Based on the historical price of investment products, traders make trading moves that maximize their portfolios. In this paper, several models are established: Model 1: Moving Average Model; Model 2: HPY Model-Calculate the Holding Profit Rate. We also utilized some economic models such as Expected Return on Investment Model to better express our opinions. We use the moving average model, set the moving average, test the optimal moving average cycle by the way of moving average, and assume the two cases of full investment in BTC and gold, judge the buy and sell trading signals of BTC and gold, and get the maximum profit rate. Next, we use the previous evidence. By comparing methods A, B and C, we worked out the situation with the highest return of gold and BTC and formulate investment strategies. In addition, we explain the relevant information of income from the point of view of economics. Finally, we find out that the sensitivity analysis shows that the algorithm has strong robustness in the case that the average model established by us receives changes in the proportion of commission, and has no impact on the strategy made by the model, but affects the results.